MR Imaging of Pleural Neoplasms. Issue 2 (April 2018) - Carter, Brett W.; Betancourt, Sonia L.; Shroff, Girish S.; Lichtenberger, John P.
Abstract : Abstract: The pleura may be affected by primary tumors or metastatic spread of intrathoracic or extrathoracic neoplasms. Primary pleural neoplasms represent ∼10% of all pleural tumors, and malignant lesions are more common than benign lesions. The most common primary tumors include malignant pleural mesothelioma and solitary fibrous tumor. Although pleural neoplasms may initially be evaluated with computed tomography (CT) and/or fluorodeoxyglucose positron emission tomography (PET)/CT, magnetic resonance (MR) imaging is complementary to these other imaging modalities for disease staging and evaluation of patients. In this article, we discuss the etiology, clinical presentation, and imaging of pleural neoplasms, with specific attention given to the role of MR imaging.